2022
DOI: 10.1097/dcr.0000000000002336
|View full text |Cite
|
Sign up to set email alerts
|

Is Polycystic Ovary Syndrome a Predisposing Factor for Pilonidal Sinus Disease?

Abstract: BACKGROUND:The incidence of pilonidal sinus may be increased in women with polycystic ovary syndrome.OBJECTIVE: This study aimed to compare the prevalence and risk factors of pilonidal sinus disease in women with and without polycystic ovary syndrome in the same population.DESIGN: This was a case-control study. SETTINGS:This study was conducted in a Turkish rural district state hospital. PATIENTS:This study included 40 female patients with polycystic ovary syndrome and 120 female patients without polycystic ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…This article highlights a novel finding of an increased risk of pilonidal sinus (PS) among women with polycystic ovary syndrome (PCOS; 22.5%) compared to the control group (1.7%). 1 This article seems to support the Karydakis theory of pilonidal sinus pathogenesis. However, recently there have been a few articles that challenge this notion.…”
Section: To the Editor—supporting
confidence: 62%
“…This article highlights a novel finding of an increased risk of pilonidal sinus (PS) among women with polycystic ovary syndrome (PCOS; 22.5%) compared to the control group (1.7%). 1 This article seems to support the Karydakis theory of pilonidal sinus pathogenesis. However, recently there have been a few articles that challenge this notion.…”
Section: To the Editor—supporting
confidence: 62%
“…Although the patient group had higher mean volume of the left ovaries, but it was at the verge of statistical significance (p=0.057). The difference in ovarian volume between the groups is likely to be explained by the more common presence of PCOS in women with PSD, and the presence of more antral follicles on the right side [ 10 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best if our knowledge, there is only one study in the literature that previously reported the relationship between PCOS and PSD. The study by Ugurlu et al [ 10 ] investigated the frequency of PSD in 40 PCOS patients compared to healthy controls, and found a statistically significant increase. On the contrary, our study examined the frequency of PCOS in patients with PSD.…”
Section: Highlight Key Pointsmentioning
confidence: 99%
“…Although most individuals with PS are diagnosed at the time of acute infection, such as an abscess causing pain and drainage, some have evidence of associated chronic disease when first observed (multiple sinuses or pits) or occult dis-ease‚ as was described in the article by Ugurlu et al 1 The goal of this Turkish study was to evaluate the prevalence of and risk factors for PS in a cohort of women with PCOS compared to those without PCOS. The hospital was in an agricultural region‚ and most of the women worked on farms in addition to doing household activities.…”
mentioning
confidence: 99%
“…T he recent medical literature has highlighted an association between polycystic ovary syndrome (PCOS) and pilonidal disease (PD) in separate studies evaluating postpubertal adolescents and women of child-bearing age, one of which has been featured in this journal. 1,2 PCOS is the most common cause of female infertility and is associated with several other comorbid conditions, including higher risks of dysfunctional uterine bleeding, endometrial carcinoma, obesity, type 2 diabetes, dyslipidemia, hypertension, and possibly cardiovascular disease, all of which can affect both quality of life and, in some cases, longevity. 3,4 The Rotterdam criteria for diagnosis of PCOS are 2 of 3 criteria of hyperandrogenism, ovulatory dysfunction, and polycystic ovaries, plus exclusion of other diagnoses that could result in hyperandrogenism (nonclassical adrenal hyperplasia, the syndromes of severe insulin resistance, androgen-secreting neoplasms, idiopathic hirsutism, and premature adrenarche) or ovulatory dysfunction (hyperprolactinemia and thyroid abnormalities).…”
mentioning
confidence: 99%